2018
DOI: 10.3390/ijerph15102175
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Heavy Metal Sources in the Soil of Riverbanks Across an Urbanization Gradient

Abstract: Regional soil quality issues arising from rapid urbanization have received extensive attention. The riverbank that runs through a city is representative of urbanization gradient transformation. Thirty soil samples in the Yangtze River Delta urban agglomeration were collected and analyzed for the concentrations of seven analytes. Correlation, principle component analysis, cluster analysis and GeoDetector models suggested that the four groups (Cr-Ni-Cu, Cu-Zn-As-Sb, Cd and Pb) shared the same sources in the core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 52 publications
(67 reference statements)
0
22
0
Order By: Relevance
“…GeoDetector is a statistical method to detect the temporal-spatial heterogeneity. This tool has been widely used in many areas, such as heavy metal differentiation, land use, and disease risk factor detection 4042 . The assumption is that, if a potential factor leads to a disease, this factor would show a temporal-spatial distribution similar to the disease.…”
Section: Methodsmentioning
confidence: 99%
“…GeoDetector is a statistical method to detect the temporal-spatial heterogeneity. This tool has been widely used in many areas, such as heavy metal differentiation, land use, and disease risk factor detection 4042 . The assumption is that, if a potential factor leads to a disease, this factor would show a temporal-spatial distribution similar to the disease.…”
Section: Methodsmentioning
confidence: 99%
“…The interaction detector in the geographical detector method can be used to examine whether two (or more) factors ( X 1 , X 2 ) have an interactive influence on a response variable through comparison of q values (Zuo et al 2018 ; Luo et al 2019 ). A description of the interactive relationships between two factors is tabulated in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…1 u, m, and d denote upstream, middle, and downstream of the sites, respectively. 2 1, 2, and 3 denote the three recycling procedures on 4, 11 and 18 November, respectively. 3 Shaded value indicates the number exceeds the threshold (Zn/Sr = 0.1161, Cu/Sr = 0.9871).…”
Section: Standardization Of Zn and Cu By Srmentioning
confidence: 99%
“…Many studies have confirmed that human factors and rapid urbanization can majorly affect soil pollution [1,2]. As the population densities and freshwater resources are unevenly distributed, farmers attempt to use wastewater from different human activities (i.e., industrial, commercial, and domestic activities) for crop irrigation [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation